Increased Human Growth Hormone After Oral Consumption of an Amino Acid Supplement: Results of a Randomized, Placebo-Controlled, Double-Blind, Crossover Study in Healthy Subjects. (July 2020) - Tam, Charmaine S.; Johnson, William D.; Rood, Jennifer; Heaton, Amy L.; Greenway, Frank L.
Abstract : Background: Human growth hormone (hGH) is best known for influencing bone and muscle growth, as well as body composition, but the use of recombinant hGH is controversial. Amino acids are a potentially safer alternative; however, preliminary investigations of the effects of oral amino acids on hGH release have been inconclusive. Therefore, we tested the effects of a novel blend of amino acids optimized to increase hGH release. Study Question: Does an investigational amino acid supplement affect hGH release? Study Design: This was a randomized, placebo-controlled, double-blind, crossover study that included 16 (12 men, 4 women; age 32 ± 14 years; body mass index 26.4 ± 5.0 kg/m 2 ) healthy participants. All participants received both placebo and the amino acid supplement after an overnight fast and completed all study visits. Treatment order was randomized, and each treatment was separated by a 1-week washout period. Measures and Outcomes: The primary outcomes were the percent change in hGH from baseline to 120 minutes and the area under the curve of hGH over baseline. Serum hGH was measured using enzyme-linked immunosorbent assay at baseline and 15, 30, 60, 90, and 120 minutes. Results: At 120 minutes, hGH levels increased by 682% (8-fold) from baseline and were significantly higher than placebo ( P = 0.01). In addition, a significantly higher mean area under the curve was observed for the amino acid supplement compared with the placebo [20.4 (95% confidence interval, 19.9–21.0 ng/mL) vs. 19.7 (95% confidence interval, 18.7–20.6 ng/mL); P = 0.04]. Conclusions: These results show that a single dose of the oral amino acid supplement was sufficient to significantly increase hGH levels in healthy adult men and women. Clinical Trial Registry: clinicaltrials.gov NCT01540773.